ANALISIS PENGARUH ASEAN CORPORATE GOVERNANCE SCORECARD, LEVERAGE, SIZE, GROWTH OPPORTUNITIES, DAN EARNINGS PRESSURE TERHADAP KONSERVATISME AKUNTANSI (Studi Kasus Pada Perusahaan Top Rank 50 ASEAN Corporate Governance Scorecard Di Indonesia yang terdaftar - Aes Sulastri; Sri Mulyati; Icih Icih (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2018)
The purpose of this research is to determine the effect of ASEAN corporate governance scorecard, leverage, size, growth opportunities, and earnings pressure to accounting conservatism on Top Ranking 50 Companies ASEAN Corporate Governance Scorecard. The population used in this research is Top Ranking 50 Companies ASEAN Corporate Governance Scorecard based on the assessments by Indonesian Institute for Corporate Directorship (IICD) listed in Indonesia Stock Exchange (BEI). The technique of sample selection used purposive sampling. Based on these criteria, obtained samples as much as 49 companies during the observation period 2013-2015. The analytical tool used in this study is the panel regression and hypothesis testing using t-test, f-test and the coefficient determination by used the program Eviews 9. These results indicate that the ASEAN Corporate Governance Scorecard have a significant negative effect on accounting conservatism. Leverage, size, and growth opportinities have a significant positive effect on accounting conservatism, but earnings pressure has no significant effect on accounting conservatism.